Migration routes of the endangered Oriental Stork (Ciconia boyciana) from Xingkai Lake, China, and their repeatability as revealed by GPS tracking - Zeyu Yang; Lixia Chen; Ru Jia; Hongying Xu; Yihua Wang; Xuelei Wei; Dongping Liu; Huajin Liu; Yulin Liu; Peiyu Yang; Guogang Zhang (Avian Research, 2023)
The Oriental Stork (Ciconia boyciana) is listed as ‘Endangered’ on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species and is classified as a first category nationally protected bird species in China. Understanding this species' seasonal movements and migration will facilitate effective conservation to promote its population. We tagged 27 Oriental Stork nestlings at Xingkai Lake on the Sanjiang Plain in Heilongjiang Province, China, used GPS tracking to follow them over the periods of 2014–2017 and 2019–2022, and confirmed their detailed migratory routes using the spatial analysis function of ArcGIS 10.7. We discovered four migration routes during autumn migration: one common long-distance migration route in which the storks migrated along the coastline of Bohai Bay to the middle and lower reaches of the Yangtze River for wintering, one short-distance migration route in which the storks wintered in Bohai Bay and two other migration routes in which the storks crossed the Bohai Strait around the Yellow River and wintered in South Korea. There were no significant differences in the number of migration days, residence days, migration distances, number of stopovers and average number of days spent at stopover sites between the autumn and spring migrations (P > 0.05). However, the storks migrated significantly faster in spring than in autumn (P ​= ​0.03). The same individuals did not exhibit a high degree of repetition in their migration timing and route selection in either autumn or spring migration. Even storks from the same nest exhibited considerable between-individual variation in their migration routes. Some important stopover sites were identified, especially in the Bohai Rim Region and on the Songnen Plain, and we further explored the current conservation status at these two important sites. Overall, our results contribute to the understanding of the annual migration, dispersal and protection status of the endangered Oriental Stork and provide a scientific basis for conservation decisions and the development of action plans for this species.